If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5r + -5(5 + 5r) = -5(2 + 7r) -5r + (5 * -5 + 5r * -5) = -5(2 + 7r) -5r + (-25 + -25r) = -5(2 + 7r) Reorder the terms: -25 + -5r + -25r = -5(2 + 7r) Combine like terms: -5r + -25r = -30r -25 + -30r = -5(2 + 7r) -25 + -30r = (2 * -5 + 7r * -5) -25 + -30r = (-10 + -35r) Solving -25 + -30r = -10 + -35r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '35r' to each side of the equation. -25 + -30r + 35r = -10 + -35r + 35r Combine like terms: -30r + 35r = 5r -25 + 5r = -10 + -35r + 35r Combine like terms: -35r + 35r = 0 -25 + 5r = -10 + 0 -25 + 5r = -10 Add '25' to each side of the equation. -25 + 25 + 5r = -10 + 25 Combine like terms: -25 + 25 = 0 0 + 5r = -10 + 25 5r = -10 + 25 Combine like terms: -10 + 25 = 15 5r = 15 Divide each side by '5'. r = 3 Simplifying r = 3
| -4.0x+2.7-16x=-4.6x+2.7 | | 2x-160250-160250=320420-160250 | | x^2y-X^2+4y-9=0 | | 8+(-8)=-8-8 | | 17x-4y=29 | | -5(-3.25)=4m+8 | | (2t-5)(6t+1)=(4t-3)(3t+6) | | 2c+3=3-4 | | 4(6.25)+3k=34.60 | | 2x-23+2x-17=8 | | Z^2-(i+1)*z+i=0 | | 5x*9-7=3 | | 12-5(3(-1)+2)=17 | | 9(2n)-3=4-6(3n-5) | | 3x^2-36x-27=0 | | 4m+4+7m=13+8m | | 11(-3x-2)-2(1-5x)=-7x-6x | | 5345+n=288195 | | m+3(4)=7 | | F(-3)=2x+4 | | .66m+2=1m-3 | | 53435+n=2888195 | | 4x-2(x-4)=-7+5x-6 | | 47.39=9g+3.92 | | 6+-4+2(6)=14 | | 2(4-8)=16 | | 39+7a=-6(-6a+8) | | 3-2m+3=1-2m+6 | | 14(27-92)=37 | | 90=(3x+6)+(7x+18) | | 7(d-2)=5(d+2)-2 | | 2x+1y=11 |